STUDENTS’ PERCEPTIONS ON THEIR ENGAGEMENT IN SMALL GROUP DISCUSSION - Vega Alviani; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2022)
The aims of this study were to describe how the students perceive theirengagement in small group discussions and to explain the factors that influencethe students engagement in small group discussions. A descriptive qualitativedesign was used in this study. The source of data was 25 students of Grade VIIISMP Al-Wasliyah 8 Medan. The data were analyzed by using descriptivequalitative. The results showed that (1) The students perceive their engagement insmall group discussion positively. Most of the students agreed that being engagedin small group discussion was useful for them as EFL students and agreed thatthey have followed all activities in small group discussion and given their besteffort. The students agreed that they could participate well in small groupdiscussion, and felt motivated to engage themselves. The students felt that theywere confident enough to deliver their opinions in group discussion. Besides, allof the students satisfied with their engagement in small group discussion. (2) Thefactors that influence the students in engaging in small group discussion were thestudents’ relationship with teachers, relationship with peers and classmates,students’ self-efficacy, students’ self-regulated learning, and students’ interest inlearning.